Delight Food Co. / Nurul Husna Hussin... [et al.] - Hussin, Nurulhusna; Zolkepli, Zaharatul Zuraini; Abdul Kudus, Siti Aishah; Ramli, Noorerly; Hashim, Shafinaz (2001)
Delight Food Co is a partnership company that focused on the manufacturing of sauces. They are based in Jejawi ,Kangar,Perlis. Started their first production in october 2002